Allelopathic Effect of Clover Residues on the Germination and Growth of Barely - AL-Behadili, Alaa A. J. (Iraqi Journal of Science, 2025)
A field experiment was conducted in the fields of the University of Baghdad to determine the effect of clover residues mixed with the soil in which the barley crop (Arviat variety) was planted. Residues of two varieties of clover (Red clover and Egyptian clover) were added at a rate of 3 and 6grams of plant residues. Two control treatments were also implemented with 3 and 6 grams of barley straw for comparison purposes. The results showed that the clover residues significantly reduced the germination and growth of the barley crop. However, this inhibition increased significantly when plant residues were added to the Egyptian clover variety at concentrations of 3 and 6grams, achieving inhibition in the germination of barley seeds. It achieved a clear inhibition in the growth characteristics of barley, represented by plant height, as it recorded an inhibition in the average plant height at both concentrations of (3 and 6 grams) reaching 46.27% and 26.61%, respectively. Meanwhile, the inhibition in the shoot biomass was 43.76% and 29.69%, respectively, while the inhibition in the root biomass was 50.78% and 42.81%. The results also showed an inhibition in the dry weight of the whole barley plant, consistent with what was mentioned in the results of germination rate, plant height, total green and root biomass which showed inhibition percentages of 48.18% and 37.89%, respectively for both concentrations of (3 and 6 grams) of plant residues. results indicate that as the concentration of plant residues in the clover increased, the allelopathic compounds’ effect on the clover also increased.